2019
DOI: 10.3892/ol.2019.11197
|View full text |Cite
|
Sign up to set email alerts
|

Influence mechanism of miRNA‑144 on proliferation and apoptosis of osteosarcoma cells

Abstract: Influence mechanism of miRNA-144 on proliferation and apoptosis of osteosarcoma cells was investigated. A total of 51 cases of osteosarcoma tissue samples were collected in the department of orthopedic surgery, Xuzhou Children's Hospital, Xuzhou Medical University from January 2014 to February 2017. Additionally, 48 cases of normal bone tissues were collected. qRT-PCR was used to detect the expression of miR-144. Correlation of miR-144 expression in serum and cancer tissues was detected. ROC curve was drawn to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of non-coding small RNA about 20-24 nucleotides [6,7]. By targeting mRNA, miRNAs could regulate the process of biological processes, cell proliferation, cell division, apoptosis, cell invasion, metastasis, metabolism, and tumorigenesis [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of non-coding small RNA about 20-24 nucleotides [6,7]. By targeting mRNA, miRNAs could regulate the process of biological processes, cell proliferation, cell division, apoptosis, cell invasion, metastasis, metabolism, and tumorigenesis [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it was also found that AX2 decreased the expression level of miRNA144, and the direct target gene of miR-144 was subsequently identified as mTOR ( Liu et al, 2016 ). However, miR-144 acts as a tumor suppressor gene to regulate cell proliferation, apoptosis and autophagy ( Xiao et al, 2015 ; Wang et al, 2017c ; Zhang et al, 2020b ). In addition, it is well known that mTOR is a positive feedback regulator of the PI3K/Akt/mTOR pathway.…”
Section: Ncrnas As Oncogenes or Tumor Suppressors Involved In The Ant...mentioning
confidence: 99%